Briefing: Water content determinations of peaty soils using the oven-drying method. Issue 1 (28th September 2018) - Li, Weichao; O'Kelly, Brendan C; Fang, Kunbin; Yang, Min
Abstract : In order to prevent possible charring, oxidation and (or) vaporisation of substances other than pore water, many researchers have adopted oven-drying temperature ( t ) values in the range 60–90°C for water content determinations of peat and other highly organic soils. This paper investigates the oven-drying characteristics of six very different highly decomposed peaty soils retrieved from south-west China for t values of 65, 85 and 105°C. Based on the presented experimental data, it is concluded that the standardised t value of 105°C used for testing of inorganic soil is also appropriate (and preferable to using lower t values) for routine water content determinations of these soils, which is in line with the growing consensus formed by other researchers on this topic. Further, the authors recommend a wet specimen mass of approximately 50 g and a 24 h oven-drying period in performing the oven-drying tests for t = 105°C. The paper also describes an existing approach to comparing and standardising water content values determined for the same organic soil, but on the basis of different t values, with the new data presented herein for the six Chinese soils used to strengthen its wider applicability in geotechnical engineering practice and related fields.